Expression of the recombinant enterocin E-760 in Pichia pastoris X33 and its antimicrobial activity towards Listeria monocytogenes - Nguyen, Khanh Hoang Viet; To, Lan Anh; Luong, Kim Phuong (Penerbit Universiti Kebangsaan Malaysia, 2022)
Bioactive compounds such as bacteriocins have become potent and promising alternatives to chemical food preservatives for extending food shelf-life and eliminating food loss from microbial spoilage. Enterocin E-760 is a specific bacterocin belonging to class II that possesses broad spectrum antibacterial activity against both Gram-negative and Gram-positive bacteria. In this study, the enterocin E-760 gene was fused to a His-tag and cloned into the expression vector, pPICzαA, and transformed into Escherichia coli DH5α cells. The recombinant plasmid was isolated, linearised and transformed into competent Pichia pastoris X33 cells using electroporation. The Pichia transformants were determined using PCR and expressed under methanol induction with the highest antibacterial activity of culture supernatants reaching 40 AU/mL. Enterocin E-760 exhibited a molecular weight of approximately 5.5 kDa and was detected directly on a Tricine SDS-PAGE gel containing Listeria monocytogenes ATCC 35152 after ethanol precipitation at a concentration ranging from 30% to 70%. This study represented the initial stages of research into using enterocin as a biopreservative in food processing.